Bioavailability and Assessment of Metal Contamination in Surface Sediments of Rades-Hamam Lif Coast, around Meliane River (Gulf of Tunis, Tunisia, Mediterranean Sea) - Rim Ben Amor; Asma Yahyaoui; Myriam Abidi; Lasaad Chouba; Moncef Gueddari (Journal of Chemistry)
The total concentration and the speciation of heavy metals (Pb, Cd, Cu, Zn, Ni, and Cr) in surface sediments of Rades-Hamam Lif coast were determined, with particular focus on the effect that urban and industrial waste in the Meliane river has on the estuary and coastal surface sediments of the Rades-Hamam Lif coast, off the Mediterranean Sea. Several geochemical indices were applied to assess the risk of contamination and the environmental risks of heavy metals on surface sediments. The total concentrations of these heavy metals are influenced by runoff, industrial, and urban wastewater. The Cd, Pb, Zn, and Ni are affected by anthropogenic sources, especially at the mouth of the Meliane river. The sequential extraction of Cd was presented dominantly in the exchangeable fraction and thus the high potential bioavailability. In contrast, Cr and Cu were mostly bound to the residual fraction indicating their low toxicity and bioavailability. The order of migration and transformation sequence was Cd > Pb > Ni > Zn > Cr > Cu, and the degree of pollution was Cd > Pb > Ni > Zn > Cr > Cu.